Leishmaniasis recidiva cutis of the lips mimicking granulomatous cheilitis - Özlem Ekiz; Emine Nur Rifaioglu; Bilge Bülbül Sen; Gülnaz Çulha; Tümay Özgür; Asena Çigdem Dogramaci (Wolters Kluwer Medknow Publications, 2015)
Leishmaniasis recidiva cutis (LRC) is an unusual form of acute cutaneous leishmaniasis. Herein, we present a case of LRC of the lips mimicking granulomatous cheilitis. An 8-year-old, Syrian child admitted with a swelling and disfigurement of his lips for 4 years. Abundant intra and extracellular Leishmania amastigotes were determined in the smear prepared from the lesion with Giemsa stain. Histopathology showed foamy histiocytes and leishmania parasites within the cytoplasm of macrophages in the epidermis and a dense dermal mixed type inflammatory cell infiltrate composed of lymphocytes, foamy histiocytes with multinucleated giant cells. On the basis of anamnestic data, the skin smears results, clinical and histopathologic findings, LRC was diagnosed. The patient was treated with meglumine antimoniate intramuscularly and fluconazole orally. Cryotherapy was applied to the residual papular lesions. The lesion improved markedly at the first month of the treatment.